2018
DOI: 10.1038/s41388-018-0281-5
|View full text |Cite
|
Sign up to set email alerts
|

The cancer-associated microprotein CASIMO1 controls cell proliferation and interacts with squalene epoxidase modulating lipid droplet formation

Abstract: Breast cancer is a leading cause of cancer-related death in women. Small open reading frame (sORF)-encoded proteins or microproteins constitute a new class of molecules often transcribed from presumed long non-coding RNA transcripts (lncRNAs). The translation of some of these sORFs has been confirmed, but their cellular function and importance remains largely unknown. Here, we report the identification and characterization of a novel microprotein of 10 kDa, which we named Cancer-Associated Small Integral Membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 72 publications
1
104
0
Order By: Relevance
“…The lncRNA profile of HCC was analyzed by a microarray‐based analysis of 32 primary tumor samples compared to seven normal liver tissue samples (Supporting Table ). To derive a broader set of cancer‐associated lncRNAs and to design a library of siRNAs against these candidates as a versatile tool to dissect lncRNAs in cancer, this data set was merged with results from two other cancer entities, breast ductal carcinoma and lung adenocarcinoma (all data deposited in the National Center for Biotechnology Information’s Gene Expression Omnibus). The analysis of this integrated data set yielded a total of 638 significantly dysregulated lncRNAs, mostly up‐regulated, which were used for the siRNA library design as described .…”
Section: Resultsmentioning
confidence: 99%
“…The lncRNA profile of HCC was analyzed by a microarray‐based analysis of 32 primary tumor samples compared to seven normal liver tissue samples (Supporting Table ). To derive a broader set of cancer‐associated lncRNAs and to design a library of siRNAs against these candidates as a versatile tool to dissect lncRNAs in cancer, this data set was merged with results from two other cancer entities, breast ductal carcinoma and lung adenocarcinoma (all data deposited in the National Center for Biotechnology Information’s Gene Expression Omnibus). The analysis of this integrated data set yielded a total of 638 significantly dysregulated lncRNAs, mostly up‐regulated, which were used for the siRNA library design as described .…”
Section: Resultsmentioning
confidence: 99%
“…It is increasingly being accepted that a large proportion of transcripts annotated as lncRNAs harbor smORFs and express micropeptides which may be stable enough to be functional [63][64][65]. Majority of the lncRNA products from the bifunctional or hybrid genes could be of this category and may express micropeptides which are functionally related to their canonical mRNA encoded proteins.…”
Section: Examples For Functionally Characterized Hybrid Genes Transcrmentioning
confidence: 99%
“…In our present study, our findings reveal that the lncRNA LINC00266-1 participates in the m 6 A recognition by m 6 A readers and the lncRNA LINC00266-1 exerts its m 6 A recognition regulation by encoding an oncopeptide instead of an RNA molecule. Our and previous studies showed that a limited number of lncRNAs and circRNAs could encode proteins/peptides to regulate tumorigenesis [37][38][39][40] . Our findings further confirmed that some peptides are hidden in some previously annotated lncRNAs.…”
Section: Resultsmentioning
confidence: 58%